Adsorption of methylene blue in aqueous solution by wood sawdust - Siti Hajarul Asma, Ahmad (2016)
The adsorption of dyes was studied using pre-treated wood sawdust with the aim of increasing percentage removal of dye (i.e. methyl orange (MO), methylene blue (MB) and congo red (CR)). Adsorption process is needed in the pre-treatment of textile industries wastewater to reduce huge quantity of dyes. The objective of the research is to degrade dyes in aqueous solution using different pre-treated wood sawdust as adsorbent, namely WSH2O, WSHCl and WSNaOH. All pre-treated adsorbent were subjected to a preliminary analysis and an adsorbent with the best performance selected for further adsorption study. The adsorbent, WSNaOH which was treated by using sodium hydroxide shows the best performance onto MB solution during the preliminary study and were further subjected to the subsequent adsorption process. Then, the selected adsorbent WSNaOH was testing at different operating variables such as initial pH solution, adsorbent dosage, initial dye concentration and process temperature. The optimum condition of the adsorption process was achieved at pH 7, 2.5 g L-1 of adsorbent dosage, 10 mg L-1 of initial concentration and 323K with the percentage removal of 99% of MB. This adsorbent has been measured by using Fourier Transform Infrared (FTIR) analysis thus the result represented the shift of OH, CH and COO functional groups before and after MB adsorption. Besides, the various results were obtained from the isotherm, kinetic and thermodynamic studies showed that the adsorption of MB onto wood sawdust is better described by the Type 2 Langmuir isotherm model compared to Freundlich isotherm model at R2 is 0.9493, follows a pseudo-second-order kinetic and an endothermic reaction was obtained.